Negative selection of patients for dialysis and transplantation in the United Kingdom. Issue 6424 (14th April 1984) - Challah, S; Wing, A J; Bauer, R; Morris, R W; Schroeder, S A
Abstract : In order to understand why the United Kingdom ranks low in the treatment of end stage renal failure a questionnaire investigating knowledge of current acceptance practice for dialysis and transplantation was sent to various groups of doctors throughout the country. The questionnaire comprised 16 case histories of patients with established end stage renal failure and associated social and medical problems. In each case the responding doctor was asked to indicate whether the patient would be suitable for treatment by dialysis or transplantation or both. The questionnaire was sent to a randomly selected sample of general practitioners and non-renal consultant physicians and their responses compared with those of all the nephrologists identified in the United Kingdom. The mean number of cases rejected by both general practitioners and non-renal consultant physicians was significantly higher than the number rejected by nephrologists. The findings suggest that underreferral of patients to dialysis and transplant units contributes to the current low acceptance rate of new patients into treatment programmes in the United Kingdom.